Gerakan Sekolah Cantik Tanpa Lipstik: Menanamkan Pendidikan Karakter Muslimah di Lingkungan SMAN 1 Pacet - Ravina Anggie Esna Putri; Aisyah Jihan Nurkhafiza; Tazkiyatur Rizqillah Fauzi; Saifuddin Zuhri (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The development of popular culture and social media has created new beauty standards among teenagers, especially female students, who tend to emphasize physical appearance aspects such as the use of cosmetics as a symbol of self-confidence. This phenomenon also occurs in the environment of SMAN 1 Pacet, where some female students show a dependence on lipstick and facial makeup in school activities, thus potentially shifting the values of modesty, shame (haya'), and morals from an Islamic perspective. This study aims to describe and analyze the implementation of the "Beautiful School Without Lipstick" Movement as an effort to install character education for Muslim women at SMAN 1 Pacet. This study uses a descriptive qualitative approach through observation, informal interviews, participant reflections, and post-program evaluation. The results show a positive change in the perception of female students regarding the concept of beauty, which is no longer oriented solely on external appearance, but rather on morals, modesty, personal hygiene, and value-based self-confidence. In addition, this program has an impact on reducing the use of lipstick in the environment.